(untitled) (Culturas Científicas, 2025)
The aim of this paper is to explore the problem of probabilities in quantum mechanics and how the concept of propensity has resurfaced in certain realist interpretations of this theory. Suárez (2007), Dorato and Esfeld (2010), and Lombardi and Castagnino (2008) have all defended the idea of considering probabilities as objective probabilities of the physical world, articulating them in terms of propensities. In this paper, we will seek to elucidate, firstly, what characterizes the positions that defend propensities as the most appropriate way to interpret probabilities in quantum mechanics; secondly, to specify the extent to which the various competing positions differ from one another; and finally, to defend the thesis put forward by both Lombardi and Castagnino (2008) and da Costa, Lombardi, and Lastiri (2013) that propensities are the best way to understand the role of probabilities in the quantum world. Within a property ontology such as that proposed by the Modal-Hamiltonian interpretation, propensities constitute second-order type-propensities that determine the tendency of said properties to be actualized in a preferred context of actualization.